PENGARUH PEMBERIAN AROMATERAPI PEPPERMINT TERHADAP MUAL MUNTAH PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI INSTALASI MEDIKAL RSUD ARIFIN ACHMAD - Erika Erika; Hernizah Hernizah; Khansa Rizki S; Mutia Sari; Raja Asmalinda; Siti Nurdiyanah; Syarifah Aini (Ensiklopedia of Journal, 2026)
Background: Nausea and vomiting are the most common side effects during chemotherapy and often disrupt patients' quality of life. The purpose of this implementation is to assess the effect of peppermint aromatherapy administration on reducing nausea and vomiting in cancer patients undergoing chemotherapy. The design is a one-group pretest-posttest, with implementation carried out at the Medical Installation of Arifin Achmad Hospital, Riau Province, over eight weeks, including preparation, pre-test, intervention, post-test, analysis, and dissemination. Two patients who meet the inclusion criteria participated as subjects. Human resources involved include researchers, academic supervisors, head nurses, and implementing nurses. The intervention was given through inhalation of peppermint aromatherapy using a nebulizer three times per chemotherapy cycle. Dissemination is planned through internal hospital presentations, academic forums, scientific publications, and community education. The results of the implementation showed a significant decrease in the intensity and frequency of nausea and vomiting based on RINVR measurements, accompanied by an increase in patients' subjective comfort without side effects. In conclusion, peppermint aromatherapy is effective as a non-pharmacological complementary therapy to reduce nausea and vomiting in chemotherapy patients and has the potential to be integrated into oncology nursing practice. Success evaluation was conducted through process observation, pre- and post-intervention measurements using RINVR, patient interviews, and nursing documentation audits. Data collection methods included direct observation, structured interviews, filling out RINVR instruments, and reviewing care records. This implementation supports the development of evidence-based nursing and can serve as a basis for developing SOPs for peppermint aromatherapy in the chemotherapy room.Keywords: Peppermint aromatherapy; nausea and vomiting; chemotherapy; complementary therapy; oncology nursing